Exploring the perceived benefits and challenges of teleworking in South Africa - Mpungose, Nomvelo Carol (University of the Witswatersrand, Johannesburg, 2023)
Telework has long piqued the interest of scholars and policymakers because of its potential to benefit individuals, organisations, and society as a whole. Telework has existed since the advent of information and communication technology, but despite substantial technological advancements, it did not attain mainstream use until the COVID-19 epidemic. Few studies have re-examined the employee benefits and challenges following the COVID-19 epidemic in South Africa, among the various facets of telework research. The function of employee perceptions that may favourably or unfavourably affect the adoption of telework are explored in this study. This study tackles telework success as a multidimensional term by deconstructing the benefits and challenges of telework for people and organisations from previous literature. The system based telework framework was adopted for this study in particular the employee factors. Fifteen in-depth interviews were done using the purposive sampling approach. Overall, the findings supported the system-based telework paradigm since an analysis of the findings showed that the existing employee factors are still persistent. The study found that there are additional elements that are negatively impacting telework adoption in the South African context, such as load shedding, while a decrease in expenditures favourably influences telework adoption. Based on the findings of this study, the additional factors should be incorporated into the model for future research. Teleworking proved that employees could meet their job responsibilities while being flexible with where they work. Therefore, telework should not be treated as a optional type of work to organisations, but should rather form part of the organisations competitive employee attraction and retention strategy. the study found that employees prefer a hybrid way of working therefore organisational mandates that require employees to return to working from the office on a full-time basis negatively affects the adoption of telework
A research report submitted to the Faculty of Commerce, Law and Management, University of the Witwatersrand, in partial fulfilment of the requirements for the degree of Master of Management in the field of Digital Business
Keywords: Teleworking; Telecommuting; Lockdown; Remote working; Working from home; UCTD; SDG-8: Decent work and economic growth